Investigating The Adoption Of Branding And Marketing Strategies And Their Influence On Customer Purchase Decisions - Hafeez, Abida; Rana, Sahar Latif; Fatima, Huma; Sabir, Hafsa; Shahid, Mobeen (Migration Letters, 2024)
The purpose of this paper is to investigate the effects of branding and marketing strategies on consumer decisions about purchasing a particular brand. The objectives of this study are addressed through a descriptive research design. The study’s respondents were chosen using simple random sampling. The sample size consists of 300 customers. According to the study’s findings, branding and market strategies significantly and positively affect customer purchase decisions. The study also shows that branding and marketing strategies, including brand advertisement and marketing, play a significant role in enhancing brand awareness, effective information delivery, and building trust and credibility, thereby affecting customer purchase decisions positively and significantly. Brand marketing paves the way for brands to make their products or services more accessible and convenient for customers, which, as a result, positively affects their purchase decisions. The results exhibit that brand marketing significantly and positively affects convenience and accessibility, as well as brand awareness, which has a significant impact and a positive change in customer decisions, thereby leading to business growth. The findings also reveal that perceived brand value, quality, brand recognition, and recall have a significant effect on customer purchase decisions, as well as that brand loyalty has a significant impact on customer decisions. Brand loyalty leads to nurturing customer relationships, resulting in lower marketing expenses and a strong emotional connection with a brand positively influences consumer buying decisions. In conclusion, brands can influence customer decisions and drive their business success and growth by implementing branding and marketing strategies.